2015
DOI: 10.4322/acr.2015.018
|View full text |Cite
|
Sign up to set email alerts
|

Gastric metastasis as the first manifestation of an invasive lobular carcinoma of the breast

Abstract: Gastrointestinal metastases from breast cancer are rare and generally occur several years after the diagnosis of the primary lesion. The diagnosis of gastric metastasis as the initial presentation of breast cancer is even rarer and can potentially mimic gastric carcinoma. We report the case of a 66-year-old female patient submitted to a total gastrectomy because of the histological diagnosis of undifferentiated gastric carcinoma. During the surgical procedure, biopsies of the peritoneum and the liver were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 23 publications
0
20
0
1
Order By: Relevance
“…Some authors recommended surgical treatment in the case of solitary gastric metastasis, followed by chemotherapy and hormonal therapy, surgical resection in these cases bringing survival benefit (67,68) or when gastric metastasis was the first symptom of lobular breast carcinoma with a long period of latency before presentation of the primary breast carcinoma (69,70).…”
Section: Therapeutic Approachmentioning
confidence: 99%
“…Some authors recommended surgical treatment in the case of solitary gastric metastasis, followed by chemotherapy and hormonal therapy, surgical resection in these cases bringing survival benefit (67,68) or when gastric metastasis was the first symptom of lobular breast carcinoma with a long period of latency before presentation of the primary breast carcinoma (69,70).…”
Section: Therapeutic Approachmentioning
confidence: 99%
“…The most common histological pattern found in gastric metastasis is adenocarcinoma with signet ring cells; this pattern can be confused with primary gastric cancer, as said in the reviews; indeed in three case reports [37][38][39] preoperative findings showed this pattern on gastric biopsies and surgical treatment was performed.…”
Section: Part 3 Comparison Between Reviews and Case Reportsmentioning
confidence: 88%
“…The preferred treatment is systemic therapy, as chemotherapy, endocrine therapy or a combination of both of them; 41 of the patients were subjected to chemotherapy with or without hormonal therapy. Combination of surgery and chemotherapy was used in 10 patients [23,28,29,35,[37][38][39]41,43,45] ; two of them [28,29] were submitted to neoadjuvant chemotherapy followed by surgery in the belief of a primary gastric cancer. Surgical treatment alone was chosen in 7 [26,27,42] patients, with three [27,42] of them in an emergency setting for bleeding and perforation.…”
Section: Therapymentioning
confidence: 99%
“…La incidencia de metástasis gastrointestinales en autopsias varía entre un 6 y un 35%. La afectación del colon se ha documentado hasta en un 12% en autopsias 10 . El estómago es el órgano más afectado.…”
Section: Discussionunclassified